ANALISIS PROSES PERENCANAAN PROGRAM PENDIDIKAN DI DINAS PENDIDIKAN PROVINSI JAWA TIMUR - Haifa’ Haifa’; Muhammad Nuril Huda; Hanun Asrohah; Anindya Palmitraazzah (STKIP Pesisir Selatan, 2026)
This study aims to analyze the process of educational program planning at the Provincial Education Office of East Java. The focus of the study includes the general overview of educational program planning, the planning process and its stages, the role of stakeholders, the challenges encountered, and innovations in planning. This research employs a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation. The results show that the educational program planning process has been carried out systematically through several stages, including needs identification, data collection, program prioritization, and budgeting. Stakeholders, such as educational institutions and local government, play a significant role in contributing data and input in the planning process. However, several challenges remain, including incomplete or outdated data and suboptimal coordination among stakeholders. To address these issues, the Education Office has implemented various strategies, such as improving coordination and utilizing digital-based information systems in planning. These innovations are expected to enhance the effectiveness and efficiency of educational program planning in the future.